Multimodal Neurological Enhancement Intervention for Self-regulation in Premature Infants. (August 2019) - Cevasco-Trotter, Andrea M.; Hamm, Ellyn L.; Yang, Xin; Parton, Jason
Abstract : Background: The neonatal intensive care unit is often a noisy, overstimulating environment that disrupts infants' regulation of physiological and behavioral states and interrupts caregiver bonding; however, infants benefit from early intervention, including the use of multimodal neurological enhancement (MMNE) intervention to provide appropriate neurodevelopmental stimulation. No one has investigated whether it assists infants in self-regulation. Purpose: The purpose of this retrospective longitudinal analysis was to examine the effect of a music therapy intervention, MMNE, on self-regulation of premature infants as measured by changes in heart rate (HR). Methods: A convenience sample of 60 premature infants received 486 MMNE sessions provided by a board-certified music therapist (MT-BC). Documentation, taken during routine clinical services, involved recording infant's HRs from the standard monitor for 3 minutes at baseline, during, and after a 20-minute MMNE intervention. Results: Infants' mean HRs were decreased during and post-MMNE sessions compared with baseline ( P < .004 and P < .001, respectively). Furthermore, infants with a baseline HR above 170 had significant decreases both during and after the MMNE session ( P < .001 for both time periods). Implications for Practice: Results of this study support the existing body of evidence showing the benefits of MMNE with premature infants. Based on our results, MMNE may help infants develop and demonstrate self-regulation as indicated by maintained HRs during and after the intervention as well as a lowered HR for infants who had high HRs prior to MMNE. Implications for Research: Further research needs to be done regarding how infants process MMNE and its potential to aid sensory processing. Abstract : Supplemental Digital Content is Available in the Text.